Analisis Framing Jawa-Sentris Terhadap Pemberitaan Calon Presiden 2024 Di Media Detik.Com Periode 25–30 Oktober - Taufik Hidayat Nasution; Wahyu Widiastuti; Nurlianti Muzni (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Java Island holds a significantly dominant percentage within Indonesia. The presence of media on Java Island plays a crucial role in shaping public perception and views regarding an event, including the 2024 Presidential election, making Java Island the epicenter of media coverage in Indonesia. This phenomenon is known as Javanese-centrism, indicating the emphasis on Java's position, considered the center and reference point of Indonesia. This research applies a qualitative approach utilizing framing analysis proposed by Robert N Entman. The model encompasses steps such as defining the problem, identifying the causes of the problem, evaluating moral decisions, and detailing problem resolution. The aim is to analyze detik.com's framing related to Javanese-centrism in the coverage of the 2024 Presidential candidates. The research sample includes 5 news articles from detik.com published between October 25th and 30th, 2023. The research findings indicate that the coverage on detik.com accentuates Java Island more, potentially raising issues of regional disparity due to the Presidential candidates' campaigns focusing solely on Java Island from October 25th to 30th. Detik.com aims for Presidential campaigns to extend to all parts of Indonesia, not solely centered on Java Island, in order to mitigate issues of centralization.